PEMANFAATAN BUAH MENGKUDU TERHADAP KUALITAS MINYAK JELANTAH SEBAGAI SUMBER BELAJAR KIMIA DI SMA KUANTAN SINGINGI - Sri Rahayu; Fitri Refelita (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2017)
AbstrackCooking oil is one food that is very needed by the whole society. The rising price of cooking oil in among society with low economics, is one of the factors causing the repeated use of cooking oil (Waste cooking oil). Using of waste cooking oil can cause poisoning, cancer and others. This research aimed to know the persentage reduction in acid number and water content, also organoleptic of the oil produced. The methods of waste cooking oil can be done by giving antioxidant to the oil. Noni fruit is one of the plant that be rich of antioxidant. 50 gram simplisia of noni added to 250 ml waste cooking oil of packadge and bulk oil. The methods of acid number by alkalimetri and measurement of water content using oven. The organoleptic tests carried out by favorite level from 25 panelists. The results of this research showed that persentage of reduction in packpage and bulk oil’s acid number were 28% and 25%. Whereas for persentage of reduction water content from each oil were 75% and 71.42%. The favorite level of color, odor and flavor were 99%, 76% and 89%. The results of the questionnaire about the feasibility of video in terms of content and appearance was 84.375%, which was included in the excellent category.Keywords: Waste Cooking Oil, Noni Fruit, Water Content, Acid Number and Organoleptic Tests.